The Paradox About the Body in the Film 'Imperfect' - Muria Endah Sokowati (Program Studi Ilmu Komunikasi Universitas Bakrie, 2020)
Imperfect: Karir, Cinta dan Timbangan (2019), a film directed by Ernest Prakasa, is successful in reaching the box office, with an attracting audience of more than 2 million. This film is an adaptation of a novel with the same title written by Meira Anastasia and Ernest Prakasa. This film has the potential to educate the audience about the body and the dangers of body shaming, but eventually, it just gets back to mere commercialization. Instead of changing the mindset, what is happening is precisely upholding today’s beauty standards.